Peran Komite Sekolah dalam Partisipasi Pembiayaan Pendidikan di MTs Al Hidayah Purwokerto Barat - Rahayuningsih, Esti; Nurfuadi (Ikatan Dai Indonesia, 2024)
This study analyzes the strategic role of the school committee in financial management at MTs Al Hidayah Purwokerto Barat, focusing on financial management processes, parental involvement, and fundraising strategies. Employing a qualitative approach with a case study design, the research applied data collection methods through in-depth interviews, observation, and financial document analysis, involving school committee members, parent administrators, and school management. Thematic analysis was used to identify significant patterns and themes. Research findings reveal that the school committee plays a crucial role in budget planning, financial supervision, and educational goal achievement. They developed innovative fundraising strategies such as charity events, bazaars, and online donation campaigns, which not only increase financial support but also strengthen community engagement. Active parental involvement through various fundraising activities proved effective in enhancing financial resources and building stronger relationships between the school and students' families. The principles of transparency and accountability serve as the primary foundation in every financial management process, enabling strict monitoring of fund usage and ensuring each allocation directly contributes to improving educational quality. The study's conclusion emphasizes that a comprehensive and participatory approach to school financial management is key to creating a sustainable and high-quality educational ecosystem.